Electrical and electronic engineering principles - Morris, Noel M. (Harlow, England : Longman Scientific and Technical, 1994)
Covers computer software for the solution of circuits and applications in both certificate and diploma courses. The software described includes SPICE (Simulation Program with Integrated Circuits Emphasis), CODAS (Control System Design and Stimulation) and PCS (Process Control Simulation).
Preface. 1. Units and the electrical circuit. 2. Basic circuit theory. 3. Electric fields and capacitance. 4. Magnetic fields and circuits. 5. Electromagnetism. 6. Alternating current and voltage. 7. Single-phase a.c. circuits and power. 8. Resonance and filter circuits. 9. Three-phase circuits. 10. The transformer. 11. Rectifier circuits and an introduction to power electronics. 12. Circuit theorems. 13. Transients in electrical circuits. 14. Electrical machines. 15. Information transmission. 16. Control principles. 17. Measuring instruments and measurements. 18. Computer software for electrical and electronic principles. Index.
Include index.
Keywords: Electrical engineering; Electronic data processing -- Engineering